HIGHEST AND BEST USAGE ANALYSIS OF THE SOUTH KALIMANTAN GOVERNOR’S OFFICE BUILDING IN BANJARMASIN - Ahmad Riduan (Lambung Mangkurat University Press, 2014)
The government of the South Kalimantan Province moved the provincial capital from Banjarmasin to Banjarbaru at the end of 2011. However, there has not been a clear decision as to what the government’s old building will be used for. One thing is clear, the utilization has to be optimized by considering the local government regulations. The aim of the research is to examine the highest and the best alternatives of utilization that can be adopted for such an asset. Non-probability sampling method was used in the research to find the alternatives. The alternatives were analyzed by using the highest and the best use analysis as the relevance test instrument for each of them. After analyzing the alternatives, the benefit-cost ratio (BCR) analysis was conducted to analyze the alternatives prior to determining their feasibility. Legal analysis, physical analysis, financial analysis, and the maximum productivity analysis were the stages conducted on the research based on highest and best use analysis. Based on the result of the research, the alternative which is feasible to do is that the building is used for other governmental or public purposes. Through the analysis, the alternative meets the criteria of the analysis as mentioned before with NPV Rp. 747,439,143 and BCR 1.024. Furthermore, according to 42.5 percent of the respondents, the building is best used for UPT offices and other institutions.